2017
DOI: 10.1159/000481249
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Benefits of High-Volume Hemofiltration in Critically Ill Pediatric Patients with Severe Sepsis: A Retrospective Cohort Study

Abstract: Aims: The study aimed to assess the clinical benefits of high-volume hemofiltration (HVHF) in pediatric patients with severe sepsis compared with standard-volume continuous veno-venous hemofiltration (CVVH). Methods: We retrospectively analyzed the medical records of 155 pediatric patients with severe sepsis admitted to the pediatric intensive care unit of Shanghai Children's Hospital from January 2010 to June 2016. A total of 93 patients were treated with HVHF and 62 patients were treated with CVVH. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 40 publications
(52 reference statements)
0
30
0
Order By: Relevance
“…The pattern of CRRT used in patients with bacterial sepsis complicated by liver dysfunction was continuous hemofiltration performed using PRISMA or PRISMA flex blood purification machine and Gambro prisma filter with an ultrafiltrate flow rate of 35–50 mL/kg/hr. The indications for initiation of continuous hemofiltration included acute kidney injury, fluid overload (> 10%), or hyperammonemia (> 100 μmol/L) as described in our previous study [ 15 ], as well as hemodynamic instability such as cardiogenic shock, septic shock and multiple organ dysfunction [ 16 , 17 ]. The patients with severe coagulation disorders (APTT > 80 s or INR > 2.5), or with biofilm allergic reaction, or with difficult to set venin catheter-access were treated with conventional therapies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pattern of CRRT used in patients with bacterial sepsis complicated by liver dysfunction was continuous hemofiltration performed using PRISMA or PRISMA flex blood purification machine and Gambro prisma filter with an ultrafiltrate flow rate of 35–50 mL/kg/hr. The indications for initiation of continuous hemofiltration included acute kidney injury, fluid overload (> 10%), or hyperammonemia (> 100 μmol/L) as described in our previous study [ 15 ], as well as hemodynamic instability such as cardiogenic shock, septic shock and multiple organ dysfunction [ 16 , 17 ]. The patients with severe coagulation disorders (APTT > 80 s or INR > 2.5), or with biofilm allergic reaction, or with difficult to set venin catheter-access were treated with conventional therapies.…”
Section: Methodsmentioning
confidence: 99%
“…According to patient body weight, we chose a 6F to 12F central venous catheters (GamCath; Gambro, Colombes, France) to construct the vascular access in the right internal jugular or femoral vein. Continuous hemofiltration was performed as described in our previous study [ 15 ]. Briefly, the saline containing 5000–10,000 IU/L heparin was used to pre-treat the filter circuit.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, there were no significant reductions in plasma levels of inflammatory mediators or in improving hemodynamic variables for HVHF. However, the incidence of hyperglycemia was significantly higher in HVHF group than in CVVH group [476] (Supplemental Table 32, Supplemental Digital Content 1, http://links .lww.com/PCC/B139).…”
Section: We Suggest Against High-volume Hemofiltration (Hvhf) Over Stmentioning
confidence: 99%
“…Theoretically, however, HVHF might be highly effective when applied to these small patients, clearing significant amounts of solutes. These concepts should be appraised in the context of the work by Miao et al [5] whose retrospective study of 155 septic children compared 93 receiving HVHF with an effluent dose of 50–70 mL/kg/h to 62 in the standard hemofiltration group (35 mL/kg/h). The paper is both remarkable and original, as few authors to date have focused specifically on pediatric dialytic dose.…”
mentioning
confidence: 99%
“…Miao et al [5] ultimately showed that the outcomes for mortality and organ dysfunction were no different for the 2 groups. The reason for this requires critical attention.…”
mentioning
confidence: 99%